1998
DOI: 10.1124/mol.54.3.525
|View full text |Cite
|
Sign up to set email alerts
|

A Dileucine Sequence and an Upstream Glutamate Residue in the Intracellular Carboxyl Terminus of the Vasopressin V2Receptor Are Essential for Cell Surface Transport in COS.M6 Cells

Abstract: Little is known concerning the intracellular transport of the G protein-coupled receptors (GPCRs). Previous studies suggested a functional role for those residues immediately preceding the conserved palmitoylated cysteine residues in the intracellular carboxyl termini of some GPCRs in cell surface transport. For the human vasopressin V2 receptor, we assessed the significance of a dileucine sequence with an upstream glutamate residue (ELRSLLCC) in mediating cell surface delivery. A series of deletion and point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 25 publications
5
137
2
Order By: Relevance
“…Previous work (18) has indicated that the di-leucine motif in the C terminus of the vasopressin V 2 receptor is important in the exiting of the receptor from the endoplasmic reticulum. In that study, single substitutions of hydrophobic leucines by hydrophobic isoleucine had no effect on V 2 receptor cell surface expression (18); however, substitution of either leucine by the polar threonine decreased cell surface expression, and the double substitution completely suppressed it.…”
Section: Effect Of I316t and I317t Mutations On Cell Surface Targetinmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work (18) has indicated that the di-leucine motif in the C terminus of the vasopressin V 2 receptor is important in the exiting of the receptor from the endoplasmic reticulum. In that study, single substitutions of hydrophobic leucines by hydrophobic isoleucine had no effect on V 2 receptor cell surface expression (18); however, substitution of either leucine by the polar threonine decreased cell surface expression, and the double substitution completely suppressed it.…”
Section: Effect Of I316t and I317t Mutations On Cell Surface Targetinmentioning
confidence: 99%
“…Acidic dihydrophobic motifs, in particular di-leucine pairs preceded by a cluster of acidic amino acids, have been shown to be sorting receptor binding sites for the GGA (Golgi-localizing, ␥-adaptin ear homology domain, ARF-interacting) proteins required for the transport of protein cargo from the trans-Golgi network to endosomes (24,25). The C-terminal dihydrophobic motif that appears in GPCRs is preceded, in many GPCRs, by a conserved acidic amino acid (18). Moreover, substitution of this residue (glutamate) by glutamine in the vasopressin V 2 receptor also blocks cell surface expression of the receptor (18).…”
Section: Effect Of I316t and I317t Mutations On Cell Surface Targetinmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal live-cell imaging (at 37 1C in 5% CO 2 in a phenol red-free medium) was carried out using a Zeiss LSM510 invert laser scanning microscope (Zeiss, Sliedrecht, Netherlands). YFP was detected with l excitation ¼ 488 nm and l emission ¼ 515À550 nm, cell surface was stained with 0.05% trypan blue (Schulein et al, 1998) and recorded with l excitation ¼ 543 nm and l emission >590 nm.…”
mentioning
confidence: 99%
“…It has been demonstrated that export from the ER is a rate-limiting step for maturation of the δ-opioid receptor [8], and accumulation of misfolded receptors in the ER is associated with the pathogenesis of human disease [9,10]. Second, GPCR export from the ER is directed by highly conserved motifs in the membrane-proximal termini [11][12][13][14][15]. We have recently identified the F(X) 6 LL motif in the C-termini required for α 2B -adrenergic (α 2B -AR) and angiotensin II type 1 receptor (AT1R) export from the ER [14,15] and the YS motif in the N-termini essential for α 2 -AR export from the Golgi [16].…”
Section: Introductionmentioning
confidence: 99%